Psychosocial Risk Factors in the Work of Managers: Systematic Review - Renier, Fabricio Aparecido (2022)
Objective. This study aims to systematize and evaluate the national and international scientific production about the psychosocial risk factors present in the work of managers and how these affect their health. Method. A systematic review of the literature was done. For its development, the guidelines for conducting a systematic review proposed by the PRISMA Protocol – Preferred Reporting Items for Systematic reviews and Meta-Analyses were followed. Results. After the process of refining the results, it was found that managers are exposed to psychosocial risks related to the categories types, and production of tasks and health and well-being. The exposure to these risk factors can trigger physical and mental changes in the health of these workers, requiring prevention and mental health promotion actions.